BLM Sumoylation Is Required for Replication Stability and Normal Fork Velocity During DNA Replication - de Renty, Christelle; Pond, Kelvin W.; Yagle, Mary K.; Ellis, Nathan A. (Frontiers in Molecular Biosciences, 2022)
BLM is sumoylated in response to replication stress. We have studied the role of BLM sumoylation in physiologically normal and replication-stressed conditions by expressing in BLM-deficient cells a BLM with SUMO acceptor-site mutations, which we refer to as SUMO-mutant BLM cells. SUMO-mutant BLM cells exhibited multiple defects in both stressed and unstressed DNA replication conditions, including, in hydroxyurea-treated cells, reduced fork restart, increased fork collapse, and increased numbers of new origins fired and, in untreated cells, slower fork velocity and increased fork instability as assayed by track-length asymmetry. We further showed by fluorescence recovery after photobleaching that SUMO-mutant BLM protein was less dynamic than normal BLM and comprised a higher immobile fraction at collapsed replication forks. BLM sumoylation has previously been linked to the recruitment of RAD51 to stressed forks in hydroxyurea-treated cells. An important unresolved question is whether the failure to efficiently recruit RAD51 is the explanation for replication stress in untreated SUMO-mutant BLM cells.